JARH WA TA’DIL TERHADAP HADITS DHA’IF POPULER: Analisis Sanad Hadits Menuntut Ilmu sampai ke Negeri China - Eksani Sani; Abdul Matin Bin Salman (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
The hadith “Seek knowledge even as far as China” is very familiar among Indonesian society and indeed throughout the world. Due to its popularity, there are many scholarly views regarding the authenticity of this hadith. Although it is widely used as a motivational tool for learning, a closer examination of its chain of narrators shows that this hadith is classified as weak (dha’if). The hadith “Seek knowledge even as far as China” is well-known in Indonesia and carries the meaning of motivating individuals not to hesitate in seeking knowledge, even if it requires traveling far. It reflects a high spirit of pursuing knowledge and an appreciation for the quality of education, even if it means undertaking a long journey to a distant land. China, as one of the oldest civilizations in the world, has long been recognized as a center of knowledge and culture. Today, China also occupies an important position in the global education system. This study aims to examine the chain of narrators (sanad) of this hadith according to the perspectives of various scholars, and to assess whether it can still serve as a motivational guideline in the present day. Hadith scholars do not accept a narration unless it has a clear sanad. This approach was developed in response to the spread of false reports attributed to the Prophet Muhammad (peace be upon him). Since then, scholars have meticulously scrutinized each chain of transmission, accepting narrations as evidence only if they meet the criteria of shahih (authentic) or hasan (good), and rejecting those that do not meet these conditions. Keyword: Seeking Knowledge, Weak Hadith, Chain of Narration atau Isnad, Criticism and Validation of Narrators